Paeonol Attenuates Methotrexate-Induced Cardiac Toxicity in Rats by Inhibiting Oxidative Stress and Suppressing TLR4-Induced NF-κB Inflammatory Pathway - Abdulla Y. Al-Taher; Mohamed A. Morsy; Rehab A. Rifaai; Nagwa M. Zenhom; Seham A. Abdel-Gaber (Mediators of Inflammation)
Methotrexate (MTX) is a commonly used chemotherapeutic agent. Oxidative stress and inflammation have been proved in the development of MTX toxicity. Paeonol is a natural phenolic compound with various pharmacological activities including antioxidant and anti-inflammatory properties. The aim of the present study was to evaluate the protective effect of paeonol against MTX-induced cardiac toxicity in rats and to evaluate the various mechanisms that underlie this effect. Paeonol (100 mg/kg) was administered orally for 10 days. MTX cardiac toxicity was induced at the end of the fifth day of the experiment, with or without paeonol pretreatment. MTX-induced cardiac damage is evidenced by a distortion in the normal cardiac histological structure, with significant oxidative and nitrosative stress shown as a significant increase in NADPH oxidase-2, malondialdehyde, and nitric oxide levels along with a decrease in reduced glutathione concentration and superoxide dismutase activity compared to the control group. MTX-induced inflammatory effects are evidenced by the increased cardiac toll-like receptor 4 (TLR4) mRNA expression and protein level as well as increased cardiac tumor necrosis factor- (TNF-) α and interleukin- (IL-) 6 levels along with increased nuclear factor- (NF-) κB/p65 immunostaining. MTX increased apoptosis as shown by the upregulation of cardiac caspase 3 immunostaining. Paeonol was able to correct the oxidative and nitrosative stress as well as the inflammatory and apoptotic parameters and restore the normal histological structure compared to MTX alone. In conclusion, paeonol has a protective effect against MTX-induced cardiac toxicity through inhibiting oxidative and nitrosative stress and suppressing the TLR4/NF-κB/TNF-α/IL-6 inflammatory pathway, as well as causing an associated reduction in the proapoptotic marker, caspase 3.